2015
DOI: 10.1039/c5md00042d
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and biodistribution of novel 99mTc labeled 4-nitroimidazole dithiocarbamate complexes as potential agents to target tumor hypoxia

Abstract: The sodium 3-(4-nitro-1H-imidazolyl)propyl dithiocarbamate (N4IPDTC) was synthesized and radiolabelled with [ 99m TcO] 3+ , [ 99m Tc≡N] 2+ and [ 99m Tc(CO) 3 ] + cores to produce 99m TcO-N4IPDTC , 99m TcN-N4IPDTC and 99m Tc(CO) 3 -N4IPDTC, respectively. All of the three complexes were prepared with high radiochemical purity and had good in vitro stability over a period of 6 h. The partition coefficient results showed that 99m TcO-N4IPDTC and 99m TcN-N4IPDTC were lipophilic, while 10 99m Tc(CO) 3 -N4IPDTC was h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Considering the SERP alone, 2‐nitroimidazole derivatives seems to be the most promising molecules to target hypoxic cells. However, a quick literature survey reveals successful use of 4‐ as well as 5‐nitroimidazole radiotracers for hypoxia targeting applications ,. These observations indicates that overall efficacy of a nitroimidazole radiotracer depends not only on SERP but other molecular parameters such lipophilicity, charge of the complex etc.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the SERP alone, 2‐nitroimidazole derivatives seems to be the most promising molecules to target hypoxic cells. However, a quick literature survey reveals successful use of 4‐ as well as 5‐nitroimidazole radiotracers for hypoxia targeting applications ,. These observations indicates that overall efficacy of a nitroimidazole radiotracer depends not only on SERP but other molecular parameters such lipophilicity, charge of the complex etc.…”
Section: Resultsmentioning
confidence: 99%
“…Considering the SERP values alone, the 2‐nitroimidazole seems to be the most suitable vector for targeting hypoxic tissues ,. However, there are instances where 4‐ or 5‐nitroimidazole complexes, having lower SERP than 2‐nitroimidazole, had shown hypoxic cell targeting in vivo ,…”
Section: Introductionmentioning
confidence: 99%
“…The 99m Tc-labeled complex was stable in vitro and in vivo in murine carcinoma S180 cells with no noticeable decomposition was observed even up to 24 h. The radiopharmaceutical ( 99m Tc-2-MBI) has significantly high renal clearance and observed to be in consistent with other 99m Tc-labeled renal agents including 99m Tc-MAG3, 99m TcMAEC and 99m Tc-EC [ 32 ]. It has been observed that 99m Tc-2-MBI has high uptake in S180 tumor bearing mice as well as tumor/muscle and tumor/blood ratio were also found to be more challenging than other 99m Tc-labeled imidazole based radiotracers reported in the literature [ 20 , 21 ]. As per concern for the uptake of radiotracer in non-targeted tissues and organs such as lungs, liver and intestine, our proposed radiotracer seems to be much superior than others at 4 h post-injection [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Alberto 2005 elaborated the coordination chemistry of monodentate and bidentate imidazole ligands with 99m Tc-tricaronyl precursor and also highlighted x-ray studies to support the structural outcomes [ 19 ]. Furthermore, Li et al, 2015 and Ruan et al, 2018 also synthesized technetium-99 m labeled 4-nitroimidazole dithiocarbamate and isocyanide derivatives, respectively as potential agents for tumor hypoxia [ 20 , 21 ]. Experimental outcomes provide fruitful evidences on utilization of benzimidazole derivatives as potential agents for targeting tumor hypoxia [ [22] , [23] , [24] , [25] ].…”
Section: Introductionmentioning
confidence: 99%
“…Several pharmacological applications of dithiocarbamate compounds have been popularized scientifically in recent decades. Due to the chemical and structural flexibility of these compounds, their use has been widely investigated as anti-carcinogenic agents [66,67,68,69,70,71,72,73,74,75,76,77], antibacterial [78,79], antiviral [80,81], antifungal [82,83], among others. In this review, we have presented and discussed the different applications of these compounds as potential antiparasitic compounds, more specifically as antitrypanosomatids-drugs against Chagas disease, leishmaniasis, and African trypanosomiasis.…”
Section: Final Considerations and Expectationsmentioning
confidence: 99%